Interactions between Obsessional Symptoms and Interpersonal Ambivalences in Psychodynamic Therapy: An Empirical Case Study - Cornelis, Shana; Desmet, Mattias; Van Nieuwenhove, Kimberly L. H. D.; Meganck, Reitske; Willemsen, Jochem; Inslegers, Ruth; Feyaerts, Jasper (Frontiers in Psychology, 2017)
The classical symptom specificity hypothesis (Blatt, 1974) particularly associates obsessional symptoms to interpersonal behavior directed at autonomy and separation from others. Cross-sectional group research, however, has yielded inconsistent findings on this predicted association, and a previous empirical case study (Cornelis et al., in press; see Chapter 2) documented obsessional pathology to be rooted in profound ambivalences between autonomous and dependent interpersonal dynamics. Therefore, in the present empirical case study, concrete operationalizations of the classical symptom specificity hypothesis are contrasted to alternative hypotheses based on the observed complexities in Chapter 2. Dynamic associations between obsessional symptoms and interpersonal functioning is further explored, aiming at further contribution to theory building (i.e., through suggestions for potential hypothesis-refinement; Stiles, 2009). Similar to the first empirical case study (Chapter 1), Consensual Qualitative Research for Case studies is used to quantitatively and qualitatively describe the longitudinal, clinical interplay between obsessional symptoms and interpersonal dynamics throughout the process of supportive-expressive psychodynamic therapy. In line with findings from Chapter 1, findings reveal close associations between obsessions and interpersonal dynamics, and therapist interventions focusing on interpersonal conflicts are documented as related to interpersonal and symptomatic alterations. Observations predominantly accord to the ambivalence-hypothesis rather than to the classical symptom specificity hypothesis. Yet, meaningful differences are observed in concrete manifestations of interpersonal ambivalences within significant relationships. Findings are again discussed in light of conceptual and methodological considerations; and limitations and future research indications are addressed.